2020
DOI: 10.1021/acssynbio.0c00401
|View full text |Cite
|
Sign up to set email alerts
|

Securing the Exchange of Synthetic Genetic Constructs Using Digital Signatures

Abstract: The field of synthetic biology relies on an evergrowing supply chain of synthetic genetic material. Technologies to secure the exchange of this material are still in their infancy. Solutions proposed thus far have focused on watermarks, a dated security approach that can be used to claim authorship, but is subject to counterfeit, and does not provide any information about the integrity of the genetic material itself. In this manuscript, we describe how data encryption and digital signature algorithms can be us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In this case, the realistic theme is not containment but tracking both the agents along their DNA and tracing them to a specific origin or designer. Methods for barcoding, tagging and watermarking strains and synthetic constructs based on unique DNA identifiers have been put in place in the last few years [170][171][172][173] that facilitates such a task that even permits access to digital twins of the biologicals at stake.…”
Section: Monitoring Efficacy and Securing The Safety Of Engineered Bi...mentioning
confidence: 99%
“…In this case, the realistic theme is not containment but tracking both the agents along their DNA and tracing them to a specific origin or designer. Methods for barcoding, tagging and watermarking strains and synthetic constructs based on unique DNA identifiers have been put in place in the last few years [170][171][172][173] that facilitates such a task that even permits access to digital twins of the biologicals at stake.…”
Section: Monitoring Efficacy and Securing The Safety Of Engineered Bi...mentioning
confidence: 99%
“…However, sometimes it is not possible to trace the synthesised sample's origins because some biotech companies want to keep some sequence information confidential to protect their intellectual properties. Gallegoset al [31] developed a method to create a digital signature for molecules of DNA to confirm the sample integrity, identity and to establish authorship with robustness to handle minor mutations.…”
Section: Available Solutionsmentioning
confidence: 99%
“…Although DNA sequences are generally designed and documented digitally, and the necessity of openly providing DNA sequences and thorough gene annotations has been discussed many times, it is not uncommon for researchers to have only a vague plasmid map and/or no reference sequence [10][11][12][13]. De novo sequence assembly is thus preferred to reference-based assembly as it can overcome reference bias and help identify unexpected mutations [1,2,11,[14][15][16]. Despite the importance of accurate plasmid sequence verification, it is often overlooked in favor of simpler "confirmation" methods, such as PCR amplification or restriction digests.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, third-generation sequencing methods that allow the sequencing of long-reads thousands of nucleotides long -as long as a plasmid itself -have been developed [3,34]. Long-read sequencing can be faster and cheaper than fragmentation-based approaches, and better resolve long, complex sequences, but it is also more error prone than its predecessors and can struggle with smaller templates [1,2,27,[41][42][43]. Recent advancements in genome assembly tools have indicated that a hybrid approach, using both short and long reads, can produce improved assemblies [23,27,42,44].…”
Section: Introductionmentioning
confidence: 99%